Effects of dietary dried distillers’ grains with solubles and NSP enzyme supplementation on growth performance, intestinal morphology, immunity, and economic efficiency in broilers - Shams-Eldin, Amr M.; Sayed-Ahmed, Ahmed; Elbestawy, Ahmed R.; Elhamouly, Moustafa; Saleh, Fuad; Fayed, Whad; Ahmed, Hamada A. (Frontiers in Veterinary Science, 2026)
IntroductionThis study evaluated the effects of incorporating varying levels of dried distillers’ grains with solubles (DDGS) and non-starch polysaccharide (NSP) enzymes into broiler diets to assess their impact on growth performance, immune function, intestinal histomorphology, and economic efficiency.MethodsA total of 240 one-day-old broiler chicks (Avian 48; initial weight 51.57 ± 4.6 g) were randomly assigned to eight dietary treatments (30 birds each). The treatments consisted of four DDGS inclusion levels (0, 5, 10%, or 20%) provided either with or without NSP enzyme supplementation.ResultsGrowth performance indicated that moderate DDGS inclusion (5–10%) with enzymes improved body weight gain and feed conversion ratio during the starter and grower phases, whereas 20% DDGS without enzymes led to poor performance. While most serum biochemical parameters remained unaffected (p > 0.05), triglycerides and globulin increased significantly (p < 0.05) in enzyme-supplemented groups. Furthermore, enzyme-supplemented groups showed significantly higher IgA and IgM levels, alongside higher white blood cell counts and H/L ratios at 5% and 10% DDGS levels. Histological examination demonstrated improved villus height and crypt structure in enzyme-supplemented diets, while 20% DDGS without enzymes negatively affected gut morphology.Discussion/ConclusionEconomically, the 5% DDGS diet with enzymes achieved the lowest cost and highest net profit, whereas the 20% DDGS group without enzymes recorded the poorest economic return. In conclusion, incorporating DDGS at 5–10% with enzyme supplementation enhances growth performance, immune stimulation, and intestinal health in broilers without compromising physiological functions.